Ammoniacal Activation of Lime Depressed Pyrite - S. Dzhamyarov; I. Grigorova; M. Ranchev; I. Nishkov (International Mineral Processing Congress, 2018)
"Chelopech concentrator (part of Dundee Precious Metals) is located in central-western Bulgaria. The current process plant utilizes conventional primary crushing and SAG mill grinding, copper and pyrite rougher and cleaner flotation stages to produce a marketable gold-rich copper and pyrite concentrates. As in the most processing plants, the pyrite depression is carried out alkaline media using lime. The subsequent activation of pyrite mineral is achieved by adding sulfuric acid, which has an adverse effect on the flotation equipment. Therefore, a series of laboratory flotation experiment for activation of lime depressed pyrite by ammonium salts, such as ammonium chloride (NH4Cl), ammonium sulfate (NH4)2SO4 and ammonium bicarbonate (NH4HCO3), have been conducted. The obtained results showed that ammonium bicarbonate proved to be the most appropriate reagent choice for pyrite mineral activation. These results are confirmed by X-ray photoelectron spectroscopy (XPS), performed to determine the surface chemistry of pyrite in its natural state, after lime treatment and subsequent treatment by NH4HCO3. The registered XPS spectra indicate that the hydrophilic phases on the pyrite surface could be efficiently removed by using the ammonium salt NH4HCO3. The industrial use of NH4HCO3 as an activator of lime-depressed pyrite is a possible alternative for sulfuric acid replacement as a most widely used pyrite activator. Flotation experiments with addition of 200, 400, 600 and 800 g/t from each of the studied ammonium salts have been conducted. Furthermore, the impact of the flotation pulp pH within the scope of 9.00 – 10.50 was also investigated. The obtained results from the laboratory flotation experiments, showed that the pyrite activation with ammonium bicarbonate is an excellent possibility for replacing the sulfuric acid as main pyrite activator reagent, in order to eliminate the gypsum accumulation during the flotation of pyrite in Chelopech concentrator.INTRODUCTION The Chelopech deposit, located about 60 km east of Sofia is one of the largest Cu-Au deposits in Europe. The ore have complicated mineralogical and chemical composition. The main ore minerals are represented by pyrite, enargite (luzonite), tennantite, chalcopyrite and bornite. The average copper content of the mined ore is about 1.1 % and the gold content is about 4.0 g/t."